2011
DOI: 10.1108/09604521111127947
|View full text |Cite
|
Sign up to set email alerts
|

Private and public voice: exploring cultural influence

Abstract: PurposeThis research adopts Hofstede's typology of culture as a framework to test for cultural differences regarding consumer verbal behaviors in the context of a service provider switching incident.Design/methodology/approachThe study includes respondents from five countries selected to provide global diversity by including cultures from Asia, Europe, South America, and North America. Cooperation from a variety of businesses was utilized in each country investigated to survey employees.FindingsFindings indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 83 publications
(132 reference statements)
0
18
0
Order By: Relevance
“…Research shows that complaining to the service provider (public) or to friends and others (private) increases when perceived unfairness is greater (Balaji & Sarkar, 2013;Casado-Diaz & Nicolau-Gonzalbez, 2009). Swanson, Frankel, Sagan, and Johansen (2011) showed that during high unfairness encounters, customers perceive greater inequity and are more likely to seek redress by complaining to the service provider. Public complaining provides an opportunity for the service provider to rectify the error and potentially create a more satisfied customer.…”
Section: Perceived Unfairnessmentioning
confidence: 97%
“…Research shows that complaining to the service provider (public) or to friends and others (private) increases when perceived unfairness is greater (Balaji & Sarkar, 2013;Casado-Diaz & Nicolau-Gonzalbez, 2009). Swanson, Frankel, Sagan, and Johansen (2011) showed that during high unfairness encounters, customers perceive greater inequity and are more likely to seek redress by complaining to the service provider. Public complaining provides an opportunity for the service provider to rectify the error and potentially create a more satisfied customer.…”
Section: Perceived Unfairnessmentioning
confidence: 97%
“…In this way, Chinese consumers would also have a tendency to stay with their current providers. Prior research also suggests that they are more likely to complain directly to a service provider, instead of generate and spread negative WOM (Swanson, Frankel, Sagan, & Johansen, ). Furthermore, high power distance and low uncertainty avoidance also make Chinese consumers less likely to spread WOM and switch providers.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…In this way, Chinese consumers would also have a tendency to stay with their current providers. Prior research also suggests that they are more likely to complain directly to a service provider, instead of generate and spread negative WOM (Swanson, Frankel, Sagan, & Johansen, 2011).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Moreover, situational factors consist of the prior experience of complaints (Jin, 2010), time lost (Dolinsky, 1994), switching convenience (Kasabov & Warlow, 2010), complaint addressee (Moliner Velázquez et al, 2010), competitor density (Tsarenko & Rooslani Tojib, 2011), inconvenience and the likelihood of successful redress (Drew, Mani, Datta, Howard, & Griffin, 2003;Jin, 2010). Finally, macro element such as culture can also affect consumer complaint behaviour (Baker, Meyer, & Chebat, 2013;Ngai, Heung, Wong, & Chan, 2007;Patterson, Cowley, & Prasongsukarn, 2006;Swanson, Frankel, Sagan, & Johansen, 2011).…”
Section: Consumer Complaint Behaviourmentioning
confidence: 99%